HUBUNGAN KONSEP DIRI DENGAN KOMUNIKASI INTERPERSONAL PESERTA DIDIK KELAS VIII DI SMP NEGERI 12 PADANG - Isabel Intan Pandini; Citra Imelda Usmaan; Triyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by issues in students’ self-concept and interpersonal communication, characterized by difficulties in self-recognition, rejection of others’ opinions, introversion, lack of empathy, and challenges in building friendships. The objectives were: (1) to describe students’ self-concept, (2) to describe their interpersonal communication, and (3) to examine the correlation between self-concept and interpersonal communication. This research employed a quantitative approach with a descriptive correlational design. The population consisted of 136 eighth-grade students at SMP Negeri 12 Padang, with a sample of 103 selected using proportional random sampling. Data were collected using questionnaires and analyzed using percentage and Pearson product-moment correlation. The results indicate that: (1) students’ self-concept is in the high category (81%), (2) interpersonal communication is in the fairly good category (61%), and (3) there is no significant relationship between self-concept and interpersonal communication (r-calculated 0.133 < r-table 0.195 at a 0.05 significance level). It is concluded that self-concept does not strongly correlate with interpersonal communication skills, suggesting that school counselors implement group guidance or classroom services focusing on improving interpersonal communication skills.